ATTITUDES AND PERCEPTIONS OF SOUTH AFRICAN MILITARY ACADEMY STUDENTS TOWARDS INFORMATION AND COMMUNICATION TECHNOLOGY AND COMPUTERS - Ariane Neethling; Jaco Renken; William Moswetsi (Scientia Militaria, 2011)
The proliferation of computer technology in both our personal and professional lives, and particularly during the last decade, has created an environment in which there are varying perceptions of, and ideas about, the value of Information and Communication Technology (ICT) and computers. In order to benefit from this, especially in a defence environment, a realistic perception about the worth of computers needs to be established. This paper presents the findings of a survey that was conducted to determine attitudes towards ICT/computers among students of the SA Military Academy. Two hypotheses were tested: (1) There are significant differences in attitude towards computers between students of different Arms of the Service; gender; academic year groups; ranks; those having previous experience with computers; and those owning a personal computer (PC); (2) There are significant differences in perception towards the value of ICT/computers between students within these groupings. In brief, the study concluded that there was a significant difference between experienced and less experienced students in the perceived value of ICT/computers in the work place and their personal lives.